Monetary policy and the chaotic structure of net cash flow from investment-operating and liquidity (2014)
Monetary policy seeks to promote economic expansions or contractions by managing interest rates or money supply. The impact of these mechanisms on businesses depends on their ability to make predictions about the development of the market and the performance and profitability of their projects. Also, interest rates impact their ability to raise funds for operations, forcing them to make changes in liabilities, operations, investments and liquidity. However, many factors affect the investments, operations and liquidity of companies and it may be that economic expansion does not result in a gradual increase in the operation or investment of companies. The unpredictable evolution of the economy leads companies to adopt conservative strategies to avoid short-term indebtedness. Monetary policy should take into account the chaotic relationship existing between the assets of companies, investments, operations and liquidity; decreasing interest rates or increasing the money supply act upon a complex structure of financial relationships in companies, resulting in high unpredictability.